Global Trends in Electronic Medical Records Education and Training in Nursing and Health Care: A Bibliometric Analysis - Rossa Hasbella; Lisa Musharyanti (Indonesian Journal of Global Health Research, 2026)
Electronic medical records are becoming a crucial part of contemporary clinical practice due to the digital revolution in healthcare. The performance of healthcare workers, particularly nurses, significantly influences the successful implementation of electronic medical records, making electronic medical records education and training a strategic aspect of the healthcare system. This study aims to analyze global trends, publication patterns, international collaborations, and key research themes related to electronic medical records education and training in nursing and healthcare. This study was conducted using bibliometric analysis using the Scopus database. A literature search was conducted on December 19, 2025, using the keywords electronic medical records and training. The selection process was based on inclusion criteria. A total of 2,472 articles from 2015 to 2025 were analyzed using Bibliometrics and VOSviewer to examine publication trends, contributing countries, citations, network visualization, and the evolution of research themes. The analysis results show that publications related to electronic medical records education and training continue to increase, with the largest contribution coming from the United States. This study demonstrates that education and training are rapidly growing and multidimensional research fields in nursing and healthcare. This study provides a scientific foundation for policy development and further research in technology-based nursing education.